2005
DOI: 10.1556/amicr.52.2005.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Peptaibols and Related Peptaibiotics ofTrichoderma

Abstract: Peptaibols and the related peptaibiotics are linear, amphipathic polypeptides. More than 300 of these secondary metabolites have been described to date. These compounds are composed of 5-20 amino acids and are generally produced in microheterogeneous mixtures. Peptaibols and peptaibiotics with unusual amino acid content are the result of non-ribosomal biosynthesis. Large multifunctional enzymes known as peptide synthetases assemble these molecules by the multiple carrier thiotemplate mechanism from a remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
99
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 112 publications
1
99
0
2
Order By: Relevance
“…Trichoderma spp., also secrete a chemically diverse range of secondary metabolites, including peptaibols, polyketides, pyrones, terpenes, and polypeptides [27,28]. A previous study reported on the significance of secondary metabolites in the antagonistic action of Trichoderma spp., against the pathogenic fungi Pythium ultimum and Rhizoctonia solani [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma spp., also secrete a chemically diverse range of secondary metabolites, including peptaibols, polyketides, pyrones, terpenes, and polypeptides [27,28]. A previous study reported on the significance of secondary metabolites in the antagonistic action of Trichoderma spp., against the pathogenic fungi Pythium ultimum and Rhizoctonia solani [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…Within the genus Trichoderma/Hypocrea, so far peptaibol subfamilies 1, 4, 5 and 9 have been described (18). Subfamily 1 (SF1) comprises about half of the known structures and includes peptides ranging from 18 to 20 residues in length.…”
mentioning
confidence: 99%
“…The role of peptaibols in sporulation and mycoparasitism has been hypothesized (24), and their involvement in induced disease resistance in plants has been demonstrated (18,(25)(26)(27). Recently, a microheterogenous mixture of 20-residue peptaibols isolated from an endophytic biocontrol strain of Trichoderma citrinoviride has been demonstrated to have antifungal activities against several important forest tree pathogens, thus implicating their role in biocontrol (28).…”
mentioning
confidence: 99%
“…Several papers about Trichoderma have reported its potential for producing antibiotic peptides and hydrolytic enzymes; however, there is no report of the use of these metabolites to control insects (4,10,24,25).…”
mentioning
confidence: 99%